ANALYSIS OF LOCAL GOVERNMENT BUDGET ALLOCATED FOR REGIONAL EXPENDITURE REALIZATION IN SOUTHEAST ACEH REGENCY - Desi Aramana; Muridha Hasan (Jurnal Ekonomi, 2023)
The budget is a financial activity plan that comprises the projected expenditure estimates in one period and the proposed sources of revenue to pay these expenditures. The budget operates as a plan that is believed to be a work guideline and gives direction, as well as objectives that must be fulfilled by future company activities. This study intends to evaluate how to manage the local government budget allocated for regional expenditure realization in Southeast Aceh Regency which has been defined, the method of analysis employed is a quantitative descriptive approach employing data collection techniques such documentary techniques, surveys and observations. The source of research data is in the form of secondary data from the Local Financial Management Board. Three years of study were done in the Southeast Aceh Regency, between 2019 and 2021. The findings of study undertaken at the Southeast Aceh Regency Local Financial Management Agency about the Analysis of Realization of Local budget Budgets demonstrate that every year there are adjustments in line with local budgets made. And the performance of local government expenditure in Southeast Aceh Regency was able to efficiently conserve the local government's budget. This is evident by the absence of achievement numbers that surpass the planned expenditure budget.